DBSCAN clustering method is applied to identify severe Traffic Accident (TA) hotpots on roads - Gershtein, Arkadiy; Terekhov, Andrey (Computer Tools in Education, 2021)
DBSCAN clustering method is applied to identify severe Traffic Accident (TA) hotpots on roads. The research examines severe TA, defined as those that led to human damage (injury or death), in the city of Newton, MA and in the entire state of Massachusetts, USA from 2013 to 2018. DBSCAN algorithm was also applied to network-constrained uniformly distributed over road network data to locate threshold in number of points per cluster so that all more populated clusters identified in real data can be treated as statistically significant. For DBSCAN algorithm two types of distance metrics, Euclidean and over Network, were compared. It is found that both distances are equivalent on scale of 10 meters, which justifies hybrid approach to clustering: using Network distance only to generate uniformly distributed points needed for Monte-Carlo simulations. All clustering can be performed using Euclidean distances which is much faster and more memory efficient. Subsequent years analysis demonstrates the extend that hotspots identified are stable and occur consecutively for several years and hence may possess predictive value.
Keywords: vehicle traﬃc accident hotspot cluster DBSCAN simulation Monte-Carlo Massachusetts